High-CLDN4 ESCC cells harbor stem-like properties and indicate for poor concurrent chemoradiation therapy response in esophageal squamous cell carcinoma. (September 2019) - Lin, Cheng-Han; Li, Hao-Yi; Liu, Yu-Peng; Kuo, Pei-Fung; Wang, Wen-Ching; Lin, Forn-Chia; Chang, Wei-Lun; Sheu, Bor-Shyang; Wang, Yi-Ching; Hung, Wan-Chun; Cheng, Hui-Chuan; Yao, Yun-Chin; et al.
Background: Esophageal squamous cell carcinoma (ESCC) is the major type of esophageal cancer in Asia and demonstrates poor survival rates following a therapeutic regimen. Methods: Cancer stem cells (CSCs) are responsible for tumor initiation, progression, and treatment failure in cancers. Therefore, identification and characterization of CSCs may help to improve clinical outcomes for ESCC patients. Tumor sphere formation assay are performed to isolate cancer stem-like ESCC cells. QRT-PCR, tumor initiation, metastasis, CCRT treatment are used to evaluate ESCC cells' stemness properties in vitro and in vivo . Results: The authors' data demonstrates that cancer stem-like ESCC cells harbored stemness characteristics including self-renewal, differentiation, and transdifferentiation, and possess tumor initiation, metastasis, and treatment inefficiency properties. For the identification of useful biomarkers of cancer stem-like ESCC cells, the authors further identified that CLDN4 was upregulated in cancer stem-like ESCC cells when compared with bulk cancer cells. High-CLDN4 cells harbored stemness and cisplatin/concurrent chemoradiation therapy (CCRT) resistance properties and a high level of CLDN4 was correlated with poor prognosis and poor CCRT response in ESCC patients. Importantly, thiamine tetrahydrofurfuryl disulfide (TTFD) decreased CLDN4 and attenuated stemness in ESCC cells, and TTFD combined with CCRT improved CCRT response in vivo . Conclusions: CLDN4 was suggested as prognostic and a CCRT response indicator for ESCC patients. TTFD combined with CCRT has potential to improve ESCC patient's clinical outcomes in the future.